2021
DOI: 10.1111/jep.13616
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals' views on factors influencing shared decision‐making in primary health care centres in Saudi Arabia: A qualitative study

Abstract: Objective To describe the perspectives of healthcare professionals regarding the implementation of Shared decision‐making (SDM) in primary healthcare centres (PHCCs) in Saudi Arabia. Methods Qualitative semi‐structured interviews were conducted with a purposive and snowball sample of healthcare professionals in PHCCs. Interviews have been recorded, transcribed, translated and thematically analysed. Themes were mapped to the COM‐B model. Results Sixteen healthcare professionals were interviewed. The data analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Health professionals must be encouraged to plan regular training in their use of SDM and to comprehend the importance of building trusting relationships with patients. Qualifying the clinician-patient relationship is critical to implementing SDM, so physicians should communicate effectively [ 87 , 88 ]. Verbal and non-verbal behavior and teach-back techniques were related to more patient-centered communication [ 37 , 49 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Health professionals must be encouraged to plan regular training in their use of SDM and to comprehend the importance of building trusting relationships with patients. Qualifying the clinician-patient relationship is critical to implementing SDM, so physicians should communicate effectively [ 87 , 88 ]. Verbal and non-verbal behavior and teach-back techniques were related to more patient-centered communication [ 37 , 49 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sharp et al (2018) observed that in organizations where speed and efficiency are highly prized, nurses tend to focus on task completion rather than holistic care, even after expressing values aligned with a person‐centered approach. In several non‐Western settings, researchers have raised questions about the cultural applicability of various aspects of person‐centered care, such as patient participation in decision‐making, noting that core elements of the concept were developed within Western contexts (Alkhaibari et al, 2023; Alsulamy et al, 2021; Khuan & Juni, 2017; Lateef & Mhlongo, 2022). Implementation of person‐centered care has been found to vary based on a wide range of factors, including the age, education, motivation, and professional outlook of care providers; the gender, level of health literacy, and social support accessible to patients; and the patterns of workload, resource availability, and management styles within organizations (Alhalal et al, 2020; Alkhaibari et al, 2023; Al‐Surimi et al, 2021; Avci & Alp Yilmaz, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Most research has been focused on factors that influence decisions made by healthcare professionals alone or the role of the clinical environment in which the decision making process takes place. [24][25][26] There is one open ended interview assessing which factors drive patients' healthcare decisions in which the researchers found that, according to healthcare professionals, healthcare…”
mentioning
confidence: 99%